2017
DOI: 10.24095/hpcdp.37.8.02
|View full text |Cite
|
Sign up to set email alerts
|

Rotating shift work associated with obesity in men from northeastern Ontario

Abstract: Introduction: While some studies have suggested associations between shift work and obesity, few have been population-based or considered multiple shift schedules. Since obesity is linked with several chronic health conditions, understanding which types of shift work influence obesity is important and additional work with more detailed exposure assessment of shift work is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0
2

Year Published

2018
2018
2025
2025

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 49 publications
1
13
0
2
Order By: Relevance
“…The association between working conditions and health has been widely recognized. Particularly, time-related work factors, such as workhours and shift work, have been reported to be associated with health issues, including obesity [1], metabolic syndrome [2], and cardiovascular disease [3]. It is crucial to develop an appropriate approach for shift workers and those working long hours to prevent diseases and promote health.…”
Section: Introductionmentioning
confidence: 99%
“…The association between working conditions and health has been widely recognized. Particularly, time-related work factors, such as workhours and shift work, have been reported to be associated with health issues, including obesity [1], metabolic syndrome [2], and cardiovascular disease [3]. It is crucial to develop an appropriate approach for shift workers and those working long hours to prevent diseases and promote health.…”
Section: Introductionmentioning
confidence: 99%
“…A consensus of the Working Time Society states that there is strong evidence linking shift work (including night work) and metabolic disorders (type 2 diabetes; metabolic syndrome) but weak evidence regarding obesity [50]. Although some studies have suggested that the night shift is potentially associated with the presence of obesity [51,52], night shifts can be part of a rotating schedule that includes day shifts, which may also play a role in the development of obesity [51]. Our sample of city daytime workers had a high level of overweight, similar to the rate reported by Chin et al [52], who analyzed several occupational factors associated with obesity and also physical activity during leisure time.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, a change in appetite-regulating endocrine signalling, which may lead to weight gain 6 , is one of the several consequences of shift work. A study by Grundy et al 7 , with 1,561 men, demonstrated an association between obesity and shift work, mainly if it includes rotating shifts. Another study, by Mazucca et al 8 , demonstrated that different anthropometric parameters related to body adiposity are associated to a greater severity of OSA in men.…”
Section: Introductionmentioning
confidence: 99%